Sales to Apparently Intoxicated Customers in Three States With Different Histories of Responsible Beverage Service Training - Buller, David B; Woodall, Gill W; Saltz, Robert; Martinez, Lila; Small, Annelise; Chirico, Noah; Cutter, Gary R (Journal of studies on alcohol and drugs, 2024)
Most states prohibit sales of alcohol to customers who are apparently intoxicated, and many require training in responsible beverage service (RBS), with the aim of reducing driving while intoxicated (DWI) and other harms. Sales to apparently intoxicated patrons were assessed in onsite alcohol sales establishments and compared across three states. A sample of 180 licensed onsite alcohol establishments was selected in California ( = 60), New Mexico ( = 60), and Washington State ( = 60). States had different RBS training histories, content, and procedures. Research confederates, trained to feign cues of intoxication, visited each establishment twice. The pseudo-intoxicated patron (PP) ordered an alcoholic beverage while displaying intoxication cues. Sale of alcohol was the primary outcome. At 179 establishments assessed, PPs were served alcohol during 56.5% of 356 visits (35.6% of establishments served and 22.6% did not serve at both visits). Alcohol sales were less frequent in New Mexico (47.9% of visits; odds ratio [OR] = 0.374, = .008) and Washington State (49.6%; OR = 0.387, = .012) than in California (72.0%). Servers less consistently refused service at both visits (6.8%) in California than New Mexico (33.9%) or Washington (27.1%), χ (4, = 177) = 16.72, = .002. Alcohol sales were higher when intoxication cues were less obvious ( < .001). Overservice of alcohol to apparently intoxicated customers was frequent and likely elevated risk of DWI and other harms. The lower sales in New Mexico and Washington than California may show that a policy approach prohibiting sales to intoxicated customers combined with well-established RBS training can reduce overservice. Further efforts are needed to reduce overservice.